2022
DOI: 10.1021/acs.orglett.2c00318
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of C8-Aminated Pyrrolo-Phenanthridines or -Indoles via Series C(sp2 or sp3)–H Activation and Fluorescence Study

Abstract: This report developed a method for the synthesis of C8-aminated pyrrolo-phenanthridines or -indoles by series ortho C(sp 2 )−H amination/ipso C(sp 2 )−H or C(sp 3 )−H arylation. Nbenzoyloxyamines, as electrophilic amination reagents, did not undergo an electrophilic substitution reaction with the pyrrole side, but they did undergo a site-selective C−H amination reaction with the benzene side via Pd/NBE catalysis. The C8-aminated pyrrolophenanthridines have strong fluorescence in solution and solid state. X-ray… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…According to the screening of reaction conditions and the mechanism study of our previous work, a possible catalytic cycle for this reaction is proposed (Scheme ). Initially, palladium acetate reacts with triphenylphosphine to form a zero valent palladium complex, and then the palladium complex and the iodobenzene undergo an oxidative addition process to produce a bivalent palladium intermediate I .…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the screening of reaction conditions and the mechanism study of our previous work, a possible catalytic cycle for this reaction is proposed (Scheme ). Initially, palladium acetate reacts with triphenylphosphine to form a zero valent palladium complex, and then the palladium complex and the iodobenzene undergo an oxidative addition process to produce a bivalent palladium intermediate I .…”
Section: Results and Discussionmentioning
confidence: 99%
“…In 2013, Dong’s group realized the first ortho-C-H amination reaction of iodobenzene using R 2 N-OBz, so the nightmare that no new type of electrophilic reagent is compatible with Pd/norbornene chemistry has been broken since 2000. In 2019, Liang and we reported the direct synthesis of C4-aminated indoles using via a Catellani and retro-Diels-Alder strategy and used this strategy to synthesize 4-piperazinylindole and a GOT1 inhibitor (Scheme d) . Therefore, the synthesis of C4-aminated carbazoles and their derivatives helps us to find ways to solve it.…”
Section: Introductionmentioning
confidence: 99%
“…The development of other ortho C–H functionalization reactions was relatively difficult, and it was not until 2013 that Dong’s research group reported the first case of aryl iodide ortho C–H amination reaction . In this report, the electrophilic amination reagent with carboxylic acid oxygen as the leaving group can undergo an oxidative addition process with the aryl-norbornyl-palladacycle (ANP) intermediate, which inspired researchers in this field. ,, Subsequently, C–H acylation, thiolation, and glycosylation were also developed.…”
Section: Introductionmentioning
confidence: 99%
“…A set of control experiments were subsequently conducted to understand the role of each component. The pivalate anion proved critical for this reaction, as the yield of 3a decreased dramatically either without pivalic acid or using Pd­(OAc) 2 instead of Pd­(OPiv) 2 as the catalyst (entries 2–3). Changing the cocatalyst N 1 * to 2-amide-substituted norbornene N 2 * led to no 3a formation, with large amounts of starting materials remaining, indicative of the importance of the ester group in N 1 * (entry 4).…”
mentioning
confidence: 99%